Acceptance of a Payment for Ecosystem Services Scheme: The Decisive Influence of Collective Action. (1st April 2017) - Del Corso, Jean-Pierre; Nguyen, Thi Dieu Phuong Geneviève; Kephaliacos, Charilaos
Abstract : As scholars have shown, acceptance is key to the success of Payment for Ecosystem Services (PES) scheme. While many studies adopt a static cost-benefit perspective, few address the social process leading to acceptance. Drawing on Suchman (1995), this article examines the legitimacy process underlying the acceptance of a PES in agriculture. In particular, the role of collective action in the legitimisation process is analysed, using a combination of qualitative and quantitative methods of discourse analysis. Data from an agro-environmental PES scheme in France on water quality shows that acceptance depends on the normative and cognitive legitimacy that actors confer upon a public policy.